Answer:
![y = -6(x - \frac{1}{2})^2 -\frac{7}{2}](https://tex.z-dn.net/?f=y%20%20%3D%20-6%28x%20-%20%5Cfrac%7B1%7D%7B2%7D%29%5E2%20-%5Cfrac%7B7%7D%7B2%7D)
Step-by-step explanation:
Given:
![y = -6x^2 + 3x + 2](https://tex.z-dn.net/?f=y%20%3D%20-6x%5E2%20%2B%203x%20%2B%202)
Required
Rewrite in vertex form
The vertex form of an equation is in form of: ![y = a(x - h)^2+ k](https://tex.z-dn.net/?f=y%20%3D%20a%28x%20-%20h%29%5E2%2B%20k)
Solving: ![y = -6x^2 + 3x + 2](https://tex.z-dn.net/?f=y%20%3D%20-6x%5E2%20%2B%203x%20%2B%202)
Subtract 2 from both sides
![y - 2 = -6x^2 + 3x + 2 - 2](https://tex.z-dn.net/?f=y%20-%202%20%3D%20-6x%5E2%20%2B%203x%20%2B%202%20-%202)
![y - 2 = -6x^2 + 3x](https://tex.z-dn.net/?f=y%20-%202%20%3D%20-6x%5E2%20%2B%203x)
Factorize expression on the right hand side by dividing through by the coefficient of x²
![y - 2 = -6(x^2 - \frac{3x}{6})](https://tex.z-dn.net/?f=y%20-%202%20%3D%20-6%28x%5E2%20-%20%5Cfrac%7B3x%7D%7B6%7D%29)
![y - 2 = -6(x^2 - \frac{x}{2})](https://tex.z-dn.net/?f=y%20-%202%20%3D%20-6%28x%5E2%20-%20%5Cfrac%7Bx%7D%7B2%7D%29)
Get a perfect square of coefficient of x; then add to both sides
------------------------------------------------------------------------------------
<em>Rough work</em>
The coefficient of x is ![\frac{-1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B-1%7D%7B2%7D)
It's square is ![(\frac{-1}{2})^2 = \frac{1}{4}](https://tex.z-dn.net/?f=%28%5Cfrac%7B-1%7D%7B2%7D%29%5E2%20%3D%20%5Cfrac%7B1%7D%7B4%7D)
Adding inside the bracket of
to give: ![-6(x^2 - \frac{x}{2} + \frac{1}{4})](https://tex.z-dn.net/?f=-6%28x%5E2%20-%20%5Cfrac%7Bx%7D%7B2%7D%20%2B%20%5Cfrac%7B1%7D%7B4%7D%29)
To balance the equation, the same expression must be added to the other side of the equation;
Equivalent expression is: ![-6(\frac{1}{4})](https://tex.z-dn.net/?f=-6%28%5Cfrac%7B1%7D%7B4%7D%29)
------------------------------------------------------------------------------------
The expression becomes
![y - 2 -6(\frac{1}{4})= -6(x^2 - \frac{x}{2} + \frac{1}{4})](https://tex.z-dn.net/?f=y%20-%202%20-6%28%5Cfrac%7B1%7D%7B4%7D%29%3D%20-6%28x%5E2%20-%20%5Cfrac%7Bx%7D%7B2%7D%20%2B%20%5Cfrac%7B1%7D%7B4%7D%29)
![y - 2 -\frac{6}{4}= -6(x^2 - \frac{x}{2} + \frac{1}{4})](https://tex.z-dn.net/?f=y%20-%202%20-%5Cfrac%7B6%7D%7B4%7D%3D%20-6%28x%5E2%20-%20%5Cfrac%7Bx%7D%7B2%7D%20%2B%20%5Cfrac%7B1%7D%7B4%7D%29)
![y - 2 -\frac{3}{2}= -6(x^2 - \frac{x}{2} + \frac{1}{4})](https://tex.z-dn.net/?f=y%20-%202%20-%5Cfrac%7B3%7D%7B2%7D%3D%20-6%28x%5E2%20-%20%5Cfrac%7Bx%7D%7B2%7D%20%2B%20%5Cfrac%7B1%7D%7B4%7D%29)
Factorize the expression on the right hand side
![y - 2 -\frac{3}{2}= -6(x - \frac{1}{2})^2](https://tex.z-dn.net/?f=y%20-%202%20-%5Cfrac%7B3%7D%7B2%7D%3D%20-6%28x%20-%20%5Cfrac%7B1%7D%7B2%7D%29%5E2)
![y - (2 +\frac{3}{2})= -6(x - \frac{1}{2})^2](https://tex.z-dn.net/?f=y%20-%20%282%20%2B%5Cfrac%7B3%7D%7B2%7D%29%3D%20-6%28x%20-%20%5Cfrac%7B1%7D%7B2%7D%29%5E2)
![y - (\frac{4+3}{2})= -6(x - \frac{1}{2})^2](https://tex.z-dn.net/?f=y%20-%20%28%5Cfrac%7B4%2B3%7D%7B2%7D%29%3D%20-6%28x%20-%20%5Cfrac%7B1%7D%7B2%7D%29%5E2)
![y - (\frac{7}{2})= -6(x - \frac{1}{2})^2](https://tex.z-dn.net/?f=y%20-%20%28%5Cfrac%7B7%7D%7B2%7D%29%3D%20-6%28x%20-%20%5Cfrac%7B1%7D%7B2%7D%29%5E2)
![y +\frac{7}{2} = -6(x - \frac{1}{2})^2](https://tex.z-dn.net/?f=y%20%20%2B%5Cfrac%7B7%7D%7B2%7D%20%3D%20-6%28x%20-%20%5Cfrac%7B1%7D%7B2%7D%29%5E2)
Make y the subject of formula
![y = -6(x - \frac{1}{2})^2 -\frac{7}{2}](https://tex.z-dn.net/?f=y%20%20%3D%20-6%28x%20-%20%5Cfrac%7B1%7D%7B2%7D%29%5E2%20-%5Cfrac%7B7%7D%7B2%7D)
<em>Solved</em>
The 95 thesis was written to speak out against the wrongdoing of the church and the pope. All of the other answers don’t necessarily make sense, because he did not write it to be famous, to be the pope, etc.
35 divided by 385 is 11. This means Vivek will earn $143 in 11 hours.
Comment if I am wrong.